STRENGTHENING ISLAMIC BEHAVIOR AND ISLAMIC PSYCHOSOCIAL IN DEVELOPING PROFESSIONAL MADRASAH TEACHERS - Syahraini Tambak; Desi Sukenti (Jurnal Cakrawala Pendidikan, 2020)
Studies on professional madrasah teachers have been widely explored, but its development from the religious aspect is still limited, while professional teachers are needed in the development of quality madrasah education. This research focused on developing professional teacher of Madrasah Aliyah by strengthening Islamic behavior and Islamic psychosocial. Using ex post facto research design and involving 397 Madrasah Aliyah teachers in 12 regencies/cities of Riau Province, Indonesia. A questionnaires were made to measure Islamic behavior and Islamic psychosocial and tests to measure professional madrasah teachers. The data were analyzed using inferential statistics. The findings of this research revealed that mastery of Islamic behavior and Islamic psychosocial contributes to developing professional madrasah teachers in carrying out teaching profession. Islamic behavior and Islamic psychosocial, specifically, is predicted to improve professional madrasah teachers. However, Islamic behavior has a higher contribution than Islamic psychosocial. This study concludes that professional madrasah teachers can be developed significantly by strengthening Islamic behavior and Islamic psychosocial in madrasah teachers. This research contributes to the Director General of Islamic Education of the Ministry of Religion of the Republic of Indonesia in taking the policy to develop professional madrasah teachers in Indonesia and design lecture materials for prospective madrasah teachers.